2017
DOI: 10.1038/ncomms14355
|View full text |Cite
|
Sign up to set email alerts
|

Axon degeneration induces glial responses through Draper-TRAF4-JNK signalling

Abstract: Draper/Ced-1/MEGF-10 is an engulfment receptor that promotes clearance of cellular debris in C. elegans, Drosophila and mammals. Draper signals through an evolutionarily conserved Src family kinase cascade to drive cytoskeletal rearrangements and target engulfment through Rac1. Glia also alter gene expression patterns in response to axonal injury but pathways mediating these responses are poorly defined. We show Draper is cell autonomously required for glial activation of transcriptional reporters after axonal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
79
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 39 publications
1
79
0
Order By: Relevance
“…In Drosophila, it is involved in developmental neuronal apoptosis during embryogenesis, but is not the main player in this process (Lee et al, 2006;Shklover et al, 2015). With respect to glial phagocytosis, the dJNK pathway has been previously shown to act downstream of Drpr only in pathological conditions such as following axonal injury in the adult brain (Lu et al, 2017;Macdonald et al, 2013) or adult ventral nerve cord (Purice et al, 2017) or concurrently with excessive neuronal death in the embryonic CNS (Shklover et al, 2015). In the normal embryonic or adult CNS, dJNK signaling is not required for glial phagocytosis (Macdonald et al, 2013;Shklover et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In Drosophila, it is involved in developmental neuronal apoptosis during embryogenesis, but is not the main player in this process (Lee et al, 2006;Shklover et al, 2015). With respect to glial phagocytosis, the dJNK pathway has been previously shown to act downstream of Drpr only in pathological conditions such as following axonal injury in the adult brain (Lu et al, 2017;Macdonald et al, 2013) or adult ventral nerve cord (Purice et al, 2017) or concurrently with excessive neuronal death in the embryonic CNS (Shklover et al, 2015). In the normal embryonic or adult CNS, dJNK signaling is not required for glial phagocytosis (Macdonald et al, 2013;Shklover et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that following axonal injury in the adult brain, Drosophila JNK (dJNK) signaling upregulates Drpr expression in glia, which consequently leads to promotion of glial phagocytosis of degenerating axons (Lu et al, ; Macdonald et al, ). Activation of the dJNK pathway during embryogenesis also increases glial phagocytic ability following neuronal death (Shklover, Mishnaevski, Levy‐Adam, & Kurant, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ensheathing glial cells also contribute to the phagocytotic clearance of neuronal debris which requires expression of Draper, TNF receptor associated factor 4 (TRAF4) and Simu/Stabilin‐2 (Awasaki et al, ; Doherty, Logan, Taşdemir, & Freeman, ; Kurant, Axelrod, Leaman, & Gaul, ; Logan et al, ; Lu et al, ; MacDonald et al, ; Watts, Schuldiner, Perrino, Larsen, & Luo, ; Ziegenfuss et al, ). In addition, some removal of neuronal debris that accumulates during axonal pruning for example in the mushroom bodies can be mediated by astrocyte‐like glial cells which then, however, use an alternative signaling pathway (Hakim, Yaniv, & Schuldiner, ; Tasdemir‐Yilmaz & Freeman, ).…”
Section: Neuropil Associated Glial Cellsmentioning
confidence: 99%
“…The term wrapping glial cell should be used for glial cells encasing only axons. These glial cells are found exclusively in the PNS where they cover the sensory and motor axons in the peripheral nerves.Ensheathing glial cells also contribute to the phagocytotic clearance of neuronal debris which requires expression of Draper, TNF receptor associated factor 4 (TRAF4) and Simu/Stabilin-2(Awasaki et al, 2006; Doherty, Logan, Taşdemir, & Freeman, 2009;Kurant, Axelrod, Leaman, & Gaul, 2008;Logan et al, 2012;Lu et al, 2017; MacDonald et al, 2006; Watts, Schuldiner, Perrino, Larsen, & Luo, 2004; Ziegenfuss et al, 2008…”
mentioning
confidence: 99%